Imaging of multiple fluorescent proteins in canopies enables synthetic biology in plants. Issue 4 (3rd December 2020) - Rigoulot, Stephen B.; Schimel, Tayler M.; Lee, Jun Hyung; Sears, Robert G.; Brabazon, Holly; Layton, Jessica S.; Li, Li; Meier, Kerry A.; Poindexter, Magen R.; Schmid, Manuel J.; Seaberry, Erin M.; Brabazon, Jared W.; et al.
Summary: Reverse genetics approaches have revolutionized plant biology and agriculture. Phenomics has the prospect of bridging plant phenotypes with genes, including transgenes, to transform agricultural fields. Genetically encoded fluorescent proteins (FPs) have revolutionized plant biology paradigms in gene expression, protein trafficking and plant physiology. While the first instance of plant canopy imaging of green fluorescent protein (GFP) was performed over 25 years ago, modern phenomics has largely ignored fluorescence as a transgene expression device despite the burgeoning FP colour palette available to plant biologists. Here, we show a new platform for stand‐off imaging of plant canopies expressing a wide variety of FP genes. The platform—the fluorescence‐inducing laser projector (FILP)—uses an ultra‐low‐noise camera to image a scene illuminated by compact diode lasers of various colours, coupled with emission filters to resolve individual FPs, to phenotype transgenic plants expressing FP genes. Each of the 20 FPs screened in plants were imaged at >3 m using FILP in a laboratory‐based laser range. We also show that pairs of co‐expressed fluorescence proteins can be imaged in canopies. The FILP system enabled a rapid synthetic promoter screen: starting from 2000 synthetic promoters transfected into protoplasts to FILP‐imaged agroinfiltrated Nicotiana benthamiana plants in a matter of weeks, which was useful to characterize a water stress‐inducible synthetic promoter. FILP canopy imaging was also accomplished for stably transformed GFP potato and in a split‐GFP assay, which illustrates the flexibility of the instrument for analysing fluorescence signals in plant canopies.